Violence and female transgression in the rural world: central Chile 1850-189 - Lozoya López, Ivette (Revista de Historia Social y de las Mentalidades, 2011)
The following work analyzes the manifestations of violence and feminine transgression in the Chilean rural space during the second half of the 19th century. in this one it is inquired about the specific manifestations that print to the crime and the moral transgression the women of the popular world. The categories raised by James Scott, defined as public discourse and hidden discourse, will be used to analyze the female actions in the field, showing that popular women publicly make use of the moral norms dictated by the elites, but in daily privacy, the Transgression of said morality is a constant that allows them material subsistence and the creation of their own codes of behavior and values that have much more to do with class identification than with a gender stereotype.
Keywords: women's transgression; Crime; Hidden Discourse; Public Discourse